Analisis Kelayakan Ekonomi dan Self-Consumption dari PLTS On-grid dan Hibrid Kapasitas 1328 kWp - Osea Zebua; Zulmiftah Huda (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2024)
Abstract — Solar energy is an alternative energy source to meet electrical energy needs. In Indonesia, rooftop solar power plants (PLTS) are widely used to meet people's electrical energy needs. However, the government's policy of limiting the use of solar energy from rooftop PLTS to serve electricity loads in the industrial sector and not allowing energy exports to the public electricity network (grid) means that households and producers providing electrical energy (prosumers) must maximize their own consumption (self-consumption) from solar energy and consider the economic feasibility of installing rooftop solar power plants. This paper aims to analyse the economic feasibility and independent consumption of on-grid and hybrid type rooftop PLTS both with 15% load and with actual load. The case study used is a PLTS with a capacity of 1,328.29 kWp with electricity load and solar panel production for two months used as a pattern for electricity load and solar panel production for a year. Economic feasibility is analysed by calculating economic feasibility parameters for the two types of rooftop PLTS, including net present value (NPV), internal rate return (IRR), profitable index (PI) and payback period (PBP). The simulation is carried out by programming using the Python programming language. The simulation results show that the level of self-consumption is greater when the electricity load served is greater and also when using batteries (hybrid PLTS). The greater the self-consumption value, the greater the economic feasibility of the rooftop PLTS to be built. Overall, on-grid rooftop solar PV is more economically feasible to install. Keywords — On-grid, hybrid, economic feasibility, self-consumption, rooftop solar power plant.